The Role of Physical Activity in Reducing Academic Stress among PJKR FIKK UNM Students - Sadzali, Muhammad; Azis, Ilham (SHOOTING: Journal of Sport, Health, and Education, 2025)
Academic stress is one of the common problems experienced by students, including students majoring in Physical Education, Health, and Recreation (PJKR). Physical activity plays an important role in maintaining physical and mental health, including stress management. This study aims to analyse the relationship between physical activity levels and academic stress among PJKR students at the Faculty of Sports Science (FIKK), Makassar State University (UNM). The research method used a quantitative approach with a correlational design. A total of 120 students were selected using simple random sampling. The instruments used were the International Physical Activity Questionnaire (IPAQ) and the Perceived Stress Scale (PSS-10). The data were analysed using Pearson's correlation. The results showed a significant negative relationship between physical activity and academic stress (r = –0.46; p < 0.01), meaning that the higher the physical activity, the lower the level of academic stress. These findings emphasise the importance of promoting physical activity as a stress management strategy for PJKR students.